Gegen den Stand der Dinge. Objekte in Museen und Ausstellungen - Ziaja, Luisa (Edition Angewandte, 2016)
Challenging the Status of Things reflects on the current shift in how museums relate to material culture. Contemporary notions in material culture studies, sociology, and art theory ascribe critical power to objects. The interdisciplinary essays examine new approaches to the conditions of production, commemorative practices, and materiality of objects in museums and exhibitions.